Hydrogen generation by alcohol reforming in a tandem cell consisting of a coupled fuel cell and electrolyser. (18th March 2020) - Zakaria, Khalid; Thimmappa, Ravikumar; Mamlouk, Mohamed; Scott, Keith
Abstract: The performance of a novel electro-reformer for the production of hydrogen by electro-reforming alcohols (methanol, ethanol and glycerol) without an external electrical energy input is described. This tandem cell consists of an alcohol fuel cell coupled directly to an alcohol reformer, negating the requirement for external electricity supply and thus reducing the cost of operation and installation. The tandem cell uses a polymer electrolyte membrane (PEM) based fuel cell and electrolyser. At 80 °C, hydrogen was generated from methanol, by the tandem PEM cell, at current densities above 200 mA cm −2, without using an external electricity supply. At this condition the electro-reformer voltage was 0.32 V at an energy input (supplied by the fuel cell component) of 0.91 kWh/Nm 3 ; i.e. less than 20% of the theoretical value for hydrogen generation by water electrolysis (4.7 kWh/Nm 3 ) with zero electrical energy input from any external power source. The hydrogen generation rate was 6.2 × 10 −4  mol (H2 ) h −1 . The hydrogen production rate of the tandem cell with ethanol and glycerol was approximately an order of magnitude lower, than that with methanol. Highlights: A novel electro-catalytic reactor for the production of low cost. Hydrogen generator for remote areas and off national electricity grid device. H2 generating costed less than 20% of the that of H2 O electrolysis. A long service life of the reactor.